Blockchain adoption in academia: Promises and challenges - Artyom Kosmarski (Journal of Open Innovation: Technology, Market, and Complexity, 2020)
Blockchain has received considerable attention recently, due to its promises of verifiable, permanent, and decentralized data handling. In 2017-2020, blockchain (and associated technologies such as smart contracts) has progressed beyond cryptocurrencies, and has been hailed as a disruptive technology for a score of industries. This study adds to the growing body of research on blockchain adoption and blockchain-driven innovation in various fields, including transport, finance, and education. However, the impact of distributed ledger technologies (DLT) on the management of science has not been systematically studied so far. This paper aims to fill the gap by studying the experience of adoption of blockchain-based solutions in academia in 2017-2020. The research is based upon a critical review of projects, relevant literature, and qualitative research: interviews (N = 24) and focus groups (N = 4) with startup founders, scholars, university executives, librarians, and IT experts from the European Union (EU), the United States of America (USA), Russia, and Belarus. Key challenges and barriers to blockchain adoption in academia are delineated: usability and security issues, legal concerns, conflict of values, and a critique of political dimensions of blockchain governance.
Keywords: 650; adoption; blockchain technology; distributed ledger; governance; science